x-7/x+7 times 2x+7/7-x how do I simplify it

Notice that in the first formula there is (x-7) in the numerator and in the second one there is (7-x)=-(x-7) in the denominator.

(x-7)/(7-x)=(x-7)/-(x-7)=-1

So (x-7)/(x+7)*(2x+7)/(7-x)

=(x-7)(2x+7)/(x+7)(7-x)

=(x-7)/(7-x)*(2x+7)/(x+7)

=-(2x+7)/(x+7)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up